The evo‐devo of molluscs: Insights from a genomic perspective. Issue 6 (14th April 2020) - Yang, Zhihui; Zhang, Lingling; Hu, Jingjie; Wang, Jing; Bao, Zhenmin; Wang, Shi
Abstract: Molluscs represent one of ancient and evolutionarily most successful groups of marine invertebrates, with a tremendous diversity of morphology, behavior, and lifestyle. Molluscs are excellent subjects for evo‐devo studies; however, understanding of the evo‐devo of molluscs has been largely hampered by incomplete fossil records and limited molecular data. Recent advancement of genomics and other technologies has greatly fueled the molluscan "evo‐devo" field, and decoding of several molluscan genomes provides unprecedented insights into molluscan biology and evolution. Here, we review the recent progress of molluscan genome sequencing as well as novel insights gained from their genomes, by emphasizing how molluscan genomics enhances our understanding of the evo‐devo of molluscs. Abstract : Recent advancement of genomics and other technologies has greatly fueled the molluscan "evo‐devo" field and this review summarizes how recent decoding of several molluscan genomes provides unprecedented insights into molluscan biology and evolution. Research Highlights: The tremendous diversity of molluscs provides excellent subjects for evo‐devo studies. Recent decoding of several molluscan genomes has remarkably enhanced our understanding of molluscan biology and evolution.